2017
DOI: 10.1111/jvim.14829
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Dogs with Progressive Myelomalacia Following Acute Intervertebral Disc Extrusion

Abstract: BackgroundProgressive myelomalacia (PMM) is a catastrophic disease associated with acute intervertebral disc extrusion (IVDE). Published data on the clinical characteristics of this disease are limited.ObjectiveTo describe the onset and progression of clinical signs of PMM in a large case cohort.AnimalsFifty‐one dogs, 18 with histopathologically confirmed PMM, 33 presumptively diagnosed based on clinical signs and diagnostic imaging.MethodsRetrospective study. Dogs with confirmed IVDE and either a histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
79
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(87 citation statements)
references
References 32 publications
4
79
1
3
Order By: Relevance
“…One retrospective study demonstrated decreased odds of successful outcome with conservative therapy, and lower owner-reported quality of life scores, with the use of corticosteroids, irrespective of dose, duration, or specific steroid administered ( 23 ). While no study provides a prospective comparison of NSAIDs vs. anti-inflammatory doses of steroids in the management of IVDE in dogs, a recent study retrospectively evaluated clinical risk factors for the development of progressive myelomalacia in deep pain negative dogs and suggested that administration of corticosteroids may have a protective effect ( 62 ). The use of steroids at anti-inflammatory doses or NSAIDs in management of canine IVDE is an area where clinical equipoise exists and while controlling for pre-treatment of dogs prior to referral would present a challenge, this question could lend itself to prospective randomized trials evaluating outcome, quality of life, and incidence of myelomalacia between the two treatments.…”
Section: The Use Of Neuroprotective Strategiesmentioning
confidence: 99%
“…One retrospective study demonstrated decreased odds of successful outcome with conservative therapy, and lower owner-reported quality of life scores, with the use of corticosteroids, irrespective of dose, duration, or specific steroid administered ( 23 ). While no study provides a prospective comparison of NSAIDs vs. anti-inflammatory doses of steroids in the management of IVDE in dogs, a recent study retrospectively evaluated clinical risk factors for the development of progressive myelomalacia in deep pain negative dogs and suggested that administration of corticosteroids may have a protective effect ( 62 ). The use of steroids at anti-inflammatory doses or NSAIDs in management of canine IVDE is an area where clinical equipoise exists and while controlling for pre-treatment of dogs prior to referral would present a challenge, this question could lend itself to prospective randomized trials evaluating outcome, quality of life, and incidence of myelomalacia between the two treatments.…”
Section: The Use Of Neuroprotective Strategiesmentioning
confidence: 99%
“…A definitive diagnosis requires post mortem evaluation of the spinal cord, but a presumptive diagnosis with a high clinical suspicion can be made based upon neurologic examination findings corroborated with magnetic resonance imaging (MRI) characteristics [36]. The clinical signs consistent with PMM are a combination of complete sensorimotor loss in the pelvic limbs and the tail, loss of spinal reflexes in the pelvic limbs, loss of abdominal tone and advancement of the caudal border of the cutaneous trunci muscle reflex (CTMR) [5, 6]. As the disease spreads to the thoracic and cervical spinal cord, progression to tetraparesis, loss of reflexes in the thoracic limbs, bilateral Horner’s syndrome and respiratory distress often arise prior to death or humane euthanasia [5].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical signs consistent with PMM are a combination of complete sensorimotor loss in the pelvic limbs and the tail, loss of spinal reflexes in the pelvic limbs, loss of abdominal tone and advancement of the caudal border of the cutaneous trunci muscle reflex (CTMR) [5, 6]. As the disease spreads to the thoracic and cervical spinal cord, progression to tetraparesis, loss of reflexes in the thoracic limbs, bilateral Horner’s syndrome and respiratory distress often arise prior to death or humane euthanasia [5]. Most dogs develop signs consistent with PMM within 48 h of presentation but although the majority progress and are euthanized within 3 days after onset of signs, a delayed progression can be observed [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extrusion of disc material (Type I intervertebral disk disease, IVDD) causes contusion and compression of the spinal cord at different magnitudes in relation to the extrusion velocity and the mass of extruded disc material (Jeffery et al, 2013). Contusive events could lead to a chain of biochemical and vascular events that could produce myelomalacia under extreme conditions (Brisson, 2010;Muguet-Chanoit et al, 2012;Fingeroth et al, 2015;Castel et al, 2017). The compression could be reverted by removing disc material.…”
Section: Introductionmentioning
confidence: 99%